Answer to comments on "Fabrication and photovoltaic conversion enhancement of graphene/n-Si Schottky barrier solar cells by electrophoretic deposition". (April 2017) - Chen, Leifeng; He, Hong
Abstract: Here, we reply to comments by Valentic et al. on our paper published in Electrochimica Acta (2014, 130: 279). They commented that Au nanoparticles played the dominant role on the whole cell's performances in our improved graphene/Si solar cell. We argued that our devices are Au-doped graphene/n-Si Schottky barrier devices, not Au nanoparticles (film)/n-Si Schottky barrier devices. During the doping process, most of the Au nanopatricles covered the surfaces of the graphene. Schottky barriers between doped graphene and n-Si dominate the total cells properties. Through doping, by adjusting and tailoring the Fermi level of the graphene, the Fermi level of n-Si can be shifted down in the graphene/Si Schottky barrier cell. They also argued that the instability of our devices were related to variation in series resistance reduced at the beginning due to slightly lowered Fermi level and increased at the end by the self-compensation by deep in-diffusion of Au nanoparticles. But for our fabricated devices, we know that an oxide layer covered the Si surface, which makes it difficult for the Au ions to diffuse into the Si layer, due to the continuous growth of SiO 2 layer on the Si surface which resulted in series resistance decreasing at first and increasing in the end.